2019
DOI: 10.1155/2019/2962154
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Numerical Simulation of the Dynamic Response of Bridges under Vibratory Compaction of Bridge Deck Asphalt Pavement

Abstract: Vibratory compaction of bridge deck pavement impacts the structural integrity of bridges to certain degrees. In this study, we analyzed the dynamic response of different types of concrete-beam bridges (continuous beam and simply supported beam) with different cross-sectional designs (T-beam and hollow-slab beam) under vibratory compaction of bridge deck asphalt pavement. The dynamic response patterns of the dynamic deformation and acceleration of bridges under pavement compaction were obtained by performing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Different vehicle speed will cause different effects on the road surface and contribute to the occurrence and evolution of distress such as rutting, cracking, and water damage to some extent (Peng et al, 2019;Dan et al, 2020). In order to investigate the change law of speed distribution, the traffic flow of eight sections of the expressway from July 2014 to June 2017 is counted, and the statistical results are shown in Figure 15.…”
Section: Distribution Characteristics Of Traffic At Different Vehicle...mentioning
confidence: 99%
“…Different vehicle speed will cause different effects on the road surface and contribute to the occurrence and evolution of distress such as rutting, cracking, and water damage to some extent (Peng et al, 2019;Dan et al, 2020). In order to investigate the change law of speed distribution, the traffic flow of eight sections of the expressway from July 2014 to June 2017 is counted, and the statistical results are shown in Figure 15.…”
Section: Distribution Characteristics Of Traffic At Different Vehicle...mentioning
confidence: 99%
“…The maximum temperature of asphalt pavements in practice is close to 70 °C (Du et al, 2018;Peng et al, 2019), and exploring higher temperatures loses its practical significance. The viscoelastic temperature range of asphalt is T g K to T g + 100 100 K. Excessively high temperatures may lead to asphalt aging and reduction of healing properties of asphalt.…”
Section: Self-healing Modelingmentioning
confidence: 99%
“…Wang et al [14] have introduced the harmonic superposition approach to provide a more realistic and effective approach to determine the pavement surface's behaviour on a concrete bridge deck, it concluded that the random surface roughness of the deck pavement had a considerable impact on the stress characteristics of the asphalt concrete layer. Peng et al [15] investigated the dynamic response of several kinds of concrete-beam bridges (continuous beam and simply supported beam) with varied cross-sectional designs (T-beam and hollow-slab beam) to assure structural safety and dependability, as well as the different vibration parameters for various bridge deck pavement configurations. Han et al [16] also has examined the combined influence of bridge surface roughness and vehicle velocity on the dynamic response of concrete bridge deck pavement (BDP) under random vehicle loads.…”
mentioning
confidence: 99%